Bladder and Sigmoid Colon Perforation with a Ball Pen in a Child: Clinical Case - Vasily P. Gavrilyuk; Oleg V. Lukin; Dmitry A. Severinov; Olga V. Padalkina (Вопросы современной педиатрии)
Background. The incidence of foreign bodies in urogenital system has increased significantly among children over the past decades. However, patients' admission for help is usually late, that leads to life-threatening complications (perforation, bleeding, peritonitis). Clinical case description. A girl, 7 years old, was taken to the admission ward of the Regional children's clinical hospital with her mother. Complaints included moderate pain in suprapubic region, discomfort during urination for 2 days before admission. Survey urogram of lower pelvis (centered on the bladder) has revealed radiopaque foreign body in the bladder, presumably ball pen refill. Emergency cystoscopy was performed. Ball pen was visualized in the bladder cavity, its refill was fixed in the bladder mucosa near its neck, whereas, blunt end, presumably, has perforated its posterior wall. Removal of the foreign body trans uretrally was not possible due to its large size and tight fixation in the bladder tissues. It was decided on case conference to perform lower midline laparotomy for adequate evaluation of lower pelvis hollow organs damage and removal of large foreign body. Infiltrate was found in the pelvis (part of greater omentum and sigmoid colon fixed to the bladder), during its separation the foreign body was removed. All detected perforations of the bladder posterior wall and sigmoid colon were sutured with vicryl sutures (two and three rows, respectively). After the surgery, we gave a talk to mother and girl about the the reasons for inserting a foreign body into the bladder. The girl reported that she did it on her own, put it through urethra, but she was afraid to admit to her mother. Clinical psychologist was consulted to evaluate psychological portrait of the child and the family. No factors that could provoke a child to act like this have been identified. The girl was discharged after restoring independent stool and diuresis. Follow-up for 3 years: the girl grows and develops by age. Conclusion. Intraluminal examination methods in the diagnosis of foreign bodies of the urinary tract play the crucial role. They allow us to quickly move from diagnostic procedure to surgical intervention. However, open surgery with interdisciplinary team is advisable as exceptional approach to treatment in case of large foreign bodies of lower urinary tract.